Penerapan Teori Behavioristik dalam Pembelajaran Agama Katolik Untuk Membentuk Karakter Siswa di Lingkungan Sekolah Dasar - Abong, Agustino (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2023)
Abtract The writing this article discusses the application of Behavioristic theory in teaching Catholism to shape the character of students in elementary schools. The subject matter in writing this article is about Behavioristic learning theory in shaping student character. The purpose of writing this article is to find out and describe the application of Behavioristic theory in teaching Catholism in elementary schools. Behavioristic theory is a concept of educational psychology in the form of an approach taken by teachers of students. This approach can provide a good stimulus to students. Behavioristic is actually a theory that emphasizes attitudes and changes in behavior as a result of a person’s concrete experience, especially for students. With the implementation of Behavioristic theory, the learning process in elementary schools, especially in Chatolic religious subject, does not make students feel bored and bored in class. In addition, the method used by the author in writing this article is though the method of literature study where each source is taken from journals, books, and notes related to Behavioristic theory. From the result of writing this article, the authors conclude that the application of Behavioristic learning theory in teaching Catholism in elementary schools is one of the benchmarks in developing good attitudes of spirituality and character for students, so that the learning process does not make students become passive.